ANALISIS KEPUTUSAN PEMBELIAN PRODUK KOSMETIK GARNIER - Muhamad Fizky Yusuf (2022)
Development in business world cannot be denided, one of which is the development in the cosmetic sector, this is marked by the emergence of many brands and type of cosmetic product that make consumers have to think about making purchasing decisions. Garnier is one of the cosmetic brands in Indonesia, especially Jakarta. The purpose of this study was to determine whether purchasing decisions for Garnier cosmetic products are influenced by trust, country of origin and product quality. this research is a qualitative research using Partial Least Square (PLS) software. The sample in this study were 120 respondents spread across the Jakarta area. Data was collected through the distribution of online questionnaires to respondents. The results of this study indicate that the country of origin variable has no effect on purchasing decisions, product quality variable affect purchasing decisions, country of origin variables affect purchasing decisions through trust, product quality variables affect putchasing decisions through trust and trust variable affect purchasing decisions